1984
DOI: 10.1152/ajpregu.1984.247.5.r786
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure control in pregnant rabbits: norepinephrine and prostaglandin interactions

Abstract: The relationship between norepinephrine (NE) and prostaglandins in the regulation of systemic blood pressure during pregnancy was examined in conscious rabbits. The arterial prostaglandin E2 (PGE2) concentration was higher in pregnant than in nonpregnant rabbits. Resting blood pressure was slightly lower in the gravid animals. The pressor response to incremental doses of intravenous NE was blunted in the pregnant rabbits. Meclofenamate, a cyclooxygenase inhibitor, failed to alter the resting blood pressure in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Indomethacin may promote antikaliuresis indirectly, by inhibition of the renin-angiotensin aldosterone axis (37). The attenuated systemic pressor response to exogenous vasoconstrictors that develops during pregnancy has been observed in many species (26,(47)(48)(49)(50)(51)(52), present study). The mechanism(s) is not clearly defined, and prereceptor, receptor, and/or postreceptor phenomena could contribute.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Indomethacin may promote antikaliuresis indirectly, by inhibition of the renin-angiotensin aldosterone axis (37). The attenuated systemic pressor response to exogenous vasoconstrictors that develops during pregnancy has been observed in many species (26,(47)(48)(49)(50)(51)(52), present study). The mechanism(s) is not clearly defined, and prereceptor, receptor, and/or postreceptor phenomena could contribute.…”
Section: Discussionsupporting
confidence: 63%
“…Hart (65,66) has shown that aortic arterial and portal venous strips from pregnant rats display a reduction in barium-induced increments of tension. These studies (50,51,(64)(65)(66), including our own, perhaps suggest that pressor responsiveness in pregnant rabbits and rats are modified by different mechanisms.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…It should however be stressed that the vasopressor responses achieved in our L-NAME-treated pregnant rats always remained smaller than those obtained in untreated non pregnant rats and that, in another study, vascular refractoriness to phenylephrine was not suppressed at all after L-NAME (Nathan et al, 1995). Thus, if NO appears to play an important role in the development of reduced vascular reactivity during pregnancy, other factors are probably also involved, e.g., vasodilator prostaglandins (Venuto et al, 1984), oestrogens (Shan et al, 1994), etc . .…”
Section: Discussionmentioning
confidence: 54%
“…ACUTELY STUDIED RABBITS: The protocol followed was described previously in similar studies (37). Briefly, general anesthesia was achieved with intravenous pentobarbital sodium (30 mg/kg).…”
Section: Physiological Studiesmentioning
confidence: 99%